[View of Heimaey From Lava Rock] - Streng, Evelyn Fiedler (1975)
Photograph of Heimaey from lava rock. The town is full of distressed white buildings with stripped red and green roofs along black hills of ash and lava. Brown and grass covered mountains surround the town on either side of the photograph. The grey ocean is visible between the mountains broken up by dark strips of land.